Zara: marketing in fast fashion: a case-study - Oliveira, Carolina Lago Barbosa Ortigão de (2014)
Zara was founded in 1975 by Amancio Ortega Gaona, soon becoming the largest and most successful chain of the Galician group Inditex (Industria de Diseño Textil) and a pioneer of the rising fashion category of Fast Fashion. Its innovative vertically-integrated strategies, combined with its emphasis on quality and demand-based offer have shaped the world of fashion and brought forth many questions on its future sustainability and growth. Zara has always relied on its store network for advertising its product offer; allowing its garments to “speak for themselves”. With the continued pressure felt in the industry, management has pressed some concerns about future company growth and creative, innovating solutions must be implemented to guarantee Zara’s future growth. The case-study narrative focuses on these issues and leaves readers with an open question regarding what decision to implement.